Electrospun Spider-net Structured Nanofibers Membrane from Homogeneous Solution of Nylon-6 and Poly (Ethylene oxide) - Jha, Manoj Kumar; Shah, Dinesh; Dhital, Khuma Sharma; Bhatta, Lok Ranjan; Joshi, Sahira; Sharma, Ram Kumar; Pant, Hem Raj (Journal of Nepal Chemical Society, 2019)
Membrane development encompasses wide range of technology areas including process and product design, materials engineering, chemical engineering, as well as interaction phenomenon. Advances in membrane technology can solve most of the global concerns related to water, air, energy, healthcare and global warming. In this study, a simple electrospinning technique was applied to prepare composite nanofibers from Nylon-6 and polyethylene oxide (PEO) blend solutions. The effect of PEO on the morphology of the fiber was investigated. It was observed that the addition of PEO in the Nylon-6 solution resulted in the formation of ultrafine nanofibers along with main the fiber, which can be considered as a spider-net-like morphology. The nano/sub-nano arrangement of the fiber resembling a three-dimensional (3D) spider-net structure enhances the mechanical strength of the resulting nanofibers as compared to the pristine Nylon-6 nanofibers.